Rancang Bangun Aplikasi Tracer Study Berbasis Web Pada Stikes Yayasan Rumah Sakit Dr. Soetomo Surabaya - Ghozaly, Achmad; Nurcahyawati, Vivine; Suhandiah, Sri (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Tracer study is one of the elements in the assessment and accreditation of academic policy making, especially in the preparation of curriculum. But in the process of the tracer study in STIKES there are some problems, and that problem is uneven distribution of questionnaires, costs a lot, waiting times filling out of the questionnaires are too long, problems possibility of mistake entering the data and the problem of data security is not guaranteed because there is no distribution of privileges. To solve that problems, STIKES need a web-based system tracer study. stakeholders can access the system to be able to answer the questionnaire quickly, so that the data from the questionnaire can be processed quickly and accurately. With this application can help the STIKES in conducting tracer easily and quickly. Stakeholders can do a tracer study questionnaire online that can be accessed anywhere. STIKES parties can see the direct results of tracer study reports and graphs based on the desired criteria.